Factors Influencing the Development of Milk Production in Agricultural Holdings (Agricultural Engineering, 2021)
Many factors influence milk production and farm development. The most critical factor determining the production is the price of sold milk and indirectly the costs connected with its production. In majority of farms, milk production is profitable. The decisive factors influencing the profitability of milk production are the balance of nutrition and ensuring the welfare of dairy herds. Equally important are the genetic characteristics of cows and proper rearing of calves. The study shows that the modernization of farms also influences the development of milk production by improving the optimization of energy use and reducing labour intensity, and overall optimization of production costs.